Portrait of Mrs A. T. Herrman - Unknown:::Creator::::::::::::
Photograph shows a portrait of Mrs. A. T. Herrman dressed in a polka dot blouse, a white jacket with polka dot trim on the collar, and a small brimmed white hat. Her jewelry consists of a choker, a very long pearl necklace, and a third mid-length necklace.